8 - Investissements directs étrangers au Maroc : impact sur la productivité totale des facteurs selon le pays d’origine (1980-2012) - Azeroual, Mohamed (Africa Development, 2021)
This article is to study the impact of foreign direct investments (FDI) on total factor productivity (TFP) in Morocco between 1980 and 2012 according to the origin of FDI. Using Vector Error Correction Model, the FDI’s originating from different countries did not have the same impact on Morocco’s TFP. Only the FDI coming from France were statistically significant and had a positive effect on total factor productivity. This is explained in part by the concentration of these investments in the industrial sector, catalyst for knowledge transfer, technological change and economic growth.